Small scale factories in the Kotte Medical Officer of health area: Occupational hazards and health problems of workers. - Samaranayake, D.B.D.L (My University, 2005)
A descriptive cross sectional study was conducted in MOH area Kotte. The entire population of factories with less than 50 workers in the area was selected for the study. The sample of workers was selected by stratified random sampling according to the number of workers per factory. The sample size calculated was 267 workers. Data collection was done using an observation schedule to assess the health hazards and welfare facilities in the factories. An interviewer administered questionnaire was administered to the factory management to identify the health related practices in the factories. The commonest hazards identified were excessive noise (80), electrical hazards (88), poor house keeping (90), poor cleanliness (57), unguarded machinery (73 and ergonomic hazards (70). Chemical safety was also found to be poor in a majority of factories using chemicals. Welfare facilities like sanitary conveniences {94), drinking water (84) and washing facilities (99) were available in most factories but they were unclean and poorly maintained in a majority of them. Safety was given a very low priority in these factories and none of them had a person responsible for safety. Only 10 of the factory managers were aware of the accident notification system and almost all the factories did not comply with it. The commonest health problems identified were musculoskeletal problems respiratory conditions (10 .5), Skin rashes (6) and eye problems (3). An annual accident rate of 146 per 1000 workers was reported. The coordinated action of labour authorities, primary health care team and the factory management is recommended to improve this situation.